From Olympia to Atlanta: a cultural-historical perspective on diet and athletic training - Grivetti, L. E.; Applegate, E. A. (The Journal of Nutrition, 1997)
Greek and Roman writers described diet and training of Olympic athletes. Lucian (A.D. 120-ca. 180) described distance and speed work in runners; Galen (A.D. 131-201) recommended ball-related exercises to train vision and the body; Philostratos (A.D. 170-249) suggested cross training by endurance running, weight training, and wrestling with animals. The ancient Greek training system, the tetrad (eta tau epsilon tau rho alpha sigma), was a four-day cycle with each day devoted to a different activity. Diogenes Laertius (died A.D. 222) wrote that Greek athletes trained on dried figs, moist cheese and wheat; then the pattern changed and focused on meat. Epictetus (2nd century A.D.) wrote that Olympic victors avoided desserts and cold water and took wine sparingly. Philostratos deprecated athletic diet in his era, a pattern based on white bread sprinkled with poppy seeds, fish and pork. Americans at the XIth Olympiad in Berlin (1936) consumed beefsteak with average daily intake of 125 grams of butter or cotton oil, three eggs, custard for dessert and 1.5 L of milk. The American pattern at Berlin was characterized by ad libitum intake of white bread, dinner rolls, fresh vegetables and salads. At Atlanta, more than 5 million meals will be served during the Olympic festival. The highly varied menu will include fresh vegetables and dips; fruits, cheeses and breads; salads; pasta, rice and fruit salads; soups; meat and seafood entrees; hot vegetables; desserts; and beverages. American Southern specialties will be served.